Pandangan majikan terhadap kursus praktikum bagi program Sarjana Muda Undang-undang (Kepujian) Universiti Utara Malaysia - Hassan, Mumtaj (Universiti Utara Malaysia, 2011)
All Universities in this world aim to produce good quality, knowledgeable and skilful graduates with some working experience in their related field. Therefore, most courses are designed to collaborate with the industry sector.A practicum course offers in the law programme is important to produce good quality education.At University Utara Malaysia, all programmes are designed to include the industry exercise or practicum as compulsory course.The main objective is to expose students to the working experience and environment as well as to enable them to practice the knowledge they have acquired during their studies in the University.The objectives of this research are (1) to identify the suitability of student placement for LL.B practicum student (2) to revise content of the practicum syllabus (3) to examine employers perception towards basic skills of LL.B students undergoing practicum (4) to examine employers perception on the standard of skill and professional practice of LL.B students doing practicum (5) to design and propose a better structure in order to fulfil the market needs.This research is carried out amongst the experience legal practitioners who were the performance assessors (in their capacity as employers) of the practicum students undergoing practical training at their court, legal firm and other placement. The sample of the research consists of 17 high courts of every state in Malaysia, 21 legal firms, 12 legal departments and a corporate company.The total number of the respondents is 51. Questionnaires were given to the relevant assessors (employers) of the students.Nevertheless, only 43 questionnaires (81.31%) were returned to the researchers; namely 12 questionnaires were from the courts which consist of High court judges, Session court judges, Magistrates and senior assistant registrars, 19 from legal firms who were the advocates and solicitors of the firms, 9 from Legal Aid Departments who were legal officers, 1 from State Legal Advisory Office and 2 from Attorney General Office. Based on the respond received from the respondents, the finding indicates that the majority of the respondents are of the opinion that the course objectives and course learning outcome are good and suitable for the course syllabus of the Practicum I and Practicum II programme. They agree that the placements provided in this course are suitable for the students. The finding also indicates that UUM, LL.B students possess good basic skills, good skill and professional practice. In addition, they also agree that the students acquire the ability to debate and possess good legal writing as well as the ability to analyse critically and logically.Further, the respondents also agree that the students possess leadership skills and discipline.